Mutations of the HFE gene in patients with Osteoporosis and arthritis - McNamara, Lynette (My University, 2002)
Iron is essential to virtually all forms of living organisms. In man, iron is implicated in a number of disease states and, in particular, iron overload is now recognised as a common disorder of iron metabolism and an important cause of morbidity. Hereditary haemochromatosis is an autosomal recessive disorder of iron metabolism characterised by excessive iron absorption from the upper gastrointestinal tract resulting in the accumulation of iron in various organs of the body. While hereditary haemochromatosis is associated with the development of diverse conditions including cardiomyopathy, diabetes, liver fibrosis and cirrhosis, penetrance is very variable. It represents one of the most common genetic disorders found in people of northern European descent. A number of genes have been shown to be implicated in the development of hereditary haemochromatosis, one of which, the HFE gene, is mutated in up to 80% of patients with the disease.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree Master of Science in Medicine.